Legal Pitfalls of Incompatibility in the Workplace: An Examination of the Landmark Ruling on Racism in Rustenburg Platinum Mine v SAEWA obo Meyer Bester 2018 (5) SA 78 (CC) - Raligilia, Konanani Happy; Nxokweni, Unathi (Obiter, 2020)
In South African labour law, as is the position in other international jurisdictions, the contract of employment is founded on an employment relationship between employer and employee. This case note discusses the nature and scope of the implied term of trust and confidence in the relationship in relation to managerial employees, with particular emphasis on breach of fiduciary obligations as well as incompatibility (MacGregor “Racial Harassment in the Workplace: Context as Indicata SA Transport and Allied Workers Union obo Dlamini & Transnet Freight Rail” 2009 Industrial Law Journal 650). This obligation of mutual trust and confidence cuts both ways (Western Platinum Refinery Ltd v Hlebela (2015) 36 ILJ 2280) and means that the employer must not behave arbitrarily or unreasonably, or so as to destroy the necessary basis of mutual confidence (Malik v BCCI [1998] AC 20 35 and Woods v WM Car Services (Peterborough) Ltd 1981 IRLR 347).Since the dawn of democracy in 1994 and influenced by constitutional changes in government, South African labour law has been drastically transformed. The new government, led by the African National Congress, had to come up with a legislative framework to deal with racism. Although the Labour Relations Act 66 of 1995 (LRA) does not explicitly deal with the question of racism at work, the importance of forging harmonious employment relationships is covered in the misconduct and incapacity in Schedule 8 of the LRA (Code of Good Practice: Dismissal). To this day, racism at the workplace remains a scourge and for this reason this case note examines the Rustenburg Platinum Mine v SAEWA obo Bester 2018 (5) SA 78 (CC)) case as its focal point. The effect of racism requires that a balance be struck between an employer’s interest in managing its business as it sees fit and the employee’s interest in not being unfairly and improperly exploited.